Clockwise hysteresis of diatoms in response to nutrient dynamics during eutrophication and recovery - Manuela Milan; Nina Albrecht; Frank Peeters; Simone Wengrat; Martin Wessels; Dietmar Straile (Limnology and Oceanography, 2022)
Many lake ecosystems that have been severely disturbed by eutrophication, have also experienced large human efforts to restore “natural” conditions. However, the trajectories and the extent of recovery of these lake ecosystems are still poorly understood. In many shallow lakes, recovery was often delayed and counter‐clockwise hysteretic. Here, we study recovery and ecosystem trajectories in a large and deep lake using diatom remains in sediment cores and time series of phosphorus concentrations. We identified four periods of diatom community change: slow change during early eutrophication, thereafter a short period of rapid change after the 1950s, followed by community stability from the 1960s to the mid‐1980s, and finally a recovery phase until 2010. Diatom community structure responded quickly and in a saturating way to increasing phosphorus concentrations, but also fast to phosphorus decline. Hence, diatom community dynamics did not show counter‐clockwise hysteresis but was characterized by a high degree of recovery and clock‐wise hysteresis (CWH). We suggest that CWH in response to eutrophication and recovery is a typical and previously overlooked feature of deep lakes, which results from a more rapid change of average nutrient concentrations and thus productivity in the epilimnion compared to average nutrient concentrations across the entire water column. Such nonlinear and hysteretic responses to changing nutrients need to be considered when analyzing the effects of other stressors such as climate warming on ecosystem dynamics to prevent erroneous attribution of ecosystem change to other stressors instead of nutrient change.

Catchment scale deforestation increases the uniqueness of subtropical stream communities - Fabiana Schneck; Luis M. Bini; Adriano S. Melo; Danielle K. Petsch; Victor S. Saito; Simone Wengrat; Tadeu Siqueira (Oecologia, 2022)

Assessing the degree of ecological change and baselines for reservoirs: challenges and implications for management - Simone Wengrat; Helen Bennion; Paulo Alves de Lima Ferreira; Rubens Cesar Lopes Figueira; Denise C. Bicudo (Journal of Paleolimnology, 2019)

Paleolimnological records reveal biotic homogenization driven by eutrophication in tropical reservoirs - Simone Wengrat; Andre A. Padial; Erik Jeppesen; Thomas A. Davidson; Luciane Fontana; Sandra Costa-Böddeker; Denise C. Bicudo (Journal of Paleolimnology, 2018)